Un dimensionnement des territoires en héritage. Nouvelles tours résidentielles pour un horizon écologique incertain - Geoffrey Mollé (EchoGéo)
The new high-rise buildings planned in Europe since the 2000s crystallize the metropolization of territorial planning and the imaginary of the future. Compared to the mid-twentieth century, however, this change in scale bears witness to a significant morphological invariant: what inertia does the continued valorization of vertical architectures signal in the production conditions of tomorrow's housing? Using a variety of materials (project database, marketing materials, interviews with stakeholders), this article questions the imaginary foundations of territorial planning. It proposes to analyze its methods in the light of weighting logics between the different dimensions of the relationships that make up territories. The main hypothesis is that the permanence of high-rise buildings in past, present and future urban landscapes expresses the prevalence of institutional (legal-technical-economic) dimensions over environmental (bio-physical-chemical) and experiential (symbolic-sensory-affective) dimensions in structuring territorial evolutions. The ecological promises of territorial planning therefore appear to be dependent on the renewal of its methods, which have so far been marked by a spatio-temporal dimensioning that reduces the reality of territories to their physicality and visibility, in order to facilitate their social engineering.